Opções de manejo de Neoleucinodes elegantalis (Guenée), (Lepidoptera: Crambidae) com bases biológicas e controle mecânico, biológicos e extratos de plantas - Fragoso, Débora Ferreira Melo (2014)
The small-fruit-borer, Neoleucinodes elegantalis (Guenée) (Lepidoptera: Crambidae), is considered a major pest in tomato. Thus, management methods that assist in controlling this pest and to reduce the application of pesticides should be studied. The obje